KONSEP PENGAMANAN VIDEO CONFERENCE DENGAN ENKRIPSI AES-GCM PADA APLIKASI ZOOM - Jamaluddin Jamaluddin; Naikson Fandier Saragih; Roni Jhonson Simamora; Rimbun Siringoringo; Eviyanti Novita Purba (Universitas Methodist Indonesia, 2020)
The conditions of the Covid-19 pandemic, which began to plague at the end of 2019, brought about major changes to the patterns of interaction in society. Activities that have been carried out directly have begun to shift to activities carried out online. The use of technology, especially in applications for online interaction patterns such as video conferencing applications, is an alternative. The Zoom Cloud Meeting application is widely used by people who initially had doubts about its security system. By implementing end-to-end encryption with AES-256-GCM, it has been able to convince clients on the information security side to keep using the Zoom Cloud Meeting application.